CO2 capture in 3D-printed carbon monolith by adsorption - Henrique, Adriano (2023)
Hierarchically structured 3D-printed porous carbon monoliths were evaluated for their applicability in CO2 capture from post-combustion streams. Two materials of the same macroscopic shape were studied, which varied in the micro- and mesoporosity by changing the final CO2 activation time: activated at 1133 K for 6 h (M1) and 12 h (M2), respectively. Fixed bed breakthrough experiments with single (CO2 and N2) and multicomponent (CO2/N2: 15/85 v.%) feed mixtures were conducted, covering the temperature range of 313 - 373 K. Results demonstrated that both materials enable a thermodynamic-based separation of these components due to their strong interaction with CO2. While a higher burn-off during monolith activation enhances its adsorption capacity by increasing the surface area, the highest selectivities were obtained in M1, 18, against 10 in M2. The dual-site and standard Langmuir isotherm models conveniently fitted the adsorption equilibrium data, and a dynamic adsorption model suitably predicted the breakthrough curves.